ROLE OF LEADERSHIP, MOTIVATION, COMPETENCY, AND THE WORKING ENVIRONMENT IN IMPROVING THE ACHIEVEMENT OF STUDENTS IN AGRICULTURE, FOOD SECURITY, AND FISHERY IN KLATEN REGENCY - Winarto Winarto; Istiatin Istiatin; Kartika Hendra Titisari (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
The purpose of this study was to determine whether there is a significant influence between leadership, motivation, competence and work environment variables on employee performance. In addition, it is also to determine whether there is a significant simultaneous influence and which variable is the most dominant in influencing employee performance at the Department of Agriculture, Food Security, and Fisheries in Klaten Regency. The method used is descriptive quantitative method. The population in this study amounted to 232 employees and the sample used was 70, where the sampling technique used quota sampling. The data used are primary data and secondary data with data collection techniques: observation, documentation, questionnaire and literature study. The data analysis technique in this study used multiple linear tests. The results of the study can be concluded that: The results of the study can be concluded that: 1) There is an influence of leadership, motivation, competence and work environment simultaneously influence the performance of employees at the Department of Agriculture, Food Security, and Fisheries in Klaten Regency, 2) There is a leadership influence on achievement employees at the Department of Agriculture, Food Security, and Fisheries in Klaten Regency, 3) There is a motivational influence on the performance of employees at the Department of Agriculture, Food Security and Fisheries in Klaten Regency, 4) There is an influence of competence on employee performance at the Department of Agriculture, Food Security, and Fisheries in Klaten Regency, 5) There is an influence of the work environment on employee performance at the Department of Agriculture, Food Security and Fisheries in Klaten Regency. Keywords: Employee Achievements, Leadership, Motivation, Competence, Work Environment